Characterization of a Novel Mitovirus Infecting Melanconiella theae Isolated From Tea Plants - Shafik, Karim; Umer, Muhammad; You, Huafeng; Aboushedida, Hamdy; Wang, Zhenhua; Ni, Dejiang; Xu, Wenxing (Frontiers in Microbiology, 2021)
A dsRNA segment was identified in the fungus Melanconiella theae isolated from tea plants. The complete dsRNA sequence, determined by random cloning together with RACE protocol, is 2461 bp in length with an AU-rich content (62.37%) and comprises a single ORF of 2265-nucleotides encoding an RNA-dependent RNA-polymerase (RdRp, 754 amino acids in size). The terminus sequences can fold into predicted stable stem-loop structures. A BLASTX and phylogenetic analysis revealed the dsRNA genome shows similarities with the RdRp sequences of mitoviruses, with the highest identity of 48% with those of Grapevine-associated mitovirus 20 and Colletotrichum fructicola mitovirus 1. Our results reveal a novel member, tentatively named Melanconiella theae mitovirus 1 (MtMV1), belongs to the family Mitoviridae. MtMV1 is capsidless as examined by transmission electron microscope, efficiently transmitted through conidia as 100 conidium-generated colonies were analyzed, and easily eliminated by hyphal tipping method combined with green-leaf tea powder. MtMV1 has a genomic sequences obviously divergent from those of most members in the family Mitoviridae and some unique characteristics unreported in known members. This is the first report of a mycovirus infecting Melanconiella fungi to date.